Composite fibers of La0.5Sr0.5CoO3-δ-LaSrCoO4±δ with high catalytic activity toward oxygen reduction reaction. Issue 5 (1st April 2020) - Li, Fushao; Xu, Yingxian; Cheng, Feixiang; Yan, Yuxing; Xia, Shubiao; Liu, Jianjun; Jiang, Long
Abstract: To promote catalytic activity toward oxygen-reduction reaction in the intermediate temperature solid-oxide fuel cells, we prepared a dual-phase composite cathode material 75 mol%La0.5Sr0.5CoO3- δ -LaSrCoO4± δ with a fibrous structure via one-pot electrospinning of a polymer containing solution. We then investigated the micro-structure and electrochemical performance of this fibrous composite. The results confirm that the fibrous composite is composed of intimately mixed nano-crystalline grains and that the compositional phases are compatible with each other. Compared with the corresponding single-phase fibers, the nano-crystalline size of the composite is more stable, and the fine nano-crystalline grains are more resistant to growth and coarsening, indicating the mutual dispersion and suppression between the constituent phases. Furthermore, compared with the corresponding single-phase fibers, the electrochemical performance of this fibrous composite cathode is more favorable. At 800 °C, its area specific resistance ( ASR ) is as low as 0.03 Ω cm 2, and maximum output power density is as high as 960 mW cm −2, which is achieved from an electrolyte-supported single cell that was developed using this cathode. After aging this cathode for a long time, ASR is less worsened and the output power density decreases only slightly, indicating that the prolonged electrochemical performance in the running cells is more stable.